Răspuns :
Răspuns:
Explicație pas cu pas:
a) (- 2)(4) = (2)(- 4)
-8=-8 adevarat
e) (3)(- 2) < (3) + (- 2)
-6<3-2=1
-6<1 adevarat
b) (- 7) * 0 = - 7
0=-7 fals
(3)(- 4) < (- 3)(- 4)
-12<12 adevarat
f) (8)(- 5) > (- 5) - (8)
-40>-5-8=-13
-40>-13 fals
g) 6(- 4) < (- 6)(4)
-24<-24 fals
d) (- 10)(4) > 40
-40>40 fals
h) (- 2) * 0 >2*0
0>0 fals
stim regula semnelor:
(-)*(-)=+
(-)* (+)=-
-(+)=-
[tex]\it a)\ \ (-2)\cdot(4)=(2)\cdot(-4) \Rightarrow -8=-8\ \ (A)\\ \\ b)\ \ (-7)\cdot0=-7 \Rightarrow 0=-7\ \ (F)\\ \\ c)\ \ (3)(-4) < (-3)(-4) \Rightarrow -12 < 12\ \ (A)\\ \\ d)\ \ (-10)(4) > 40 \Rightarrow-40 > 40\ \ \ \ (F)\\ \\ \ e)\ \ (3)(-2) < 3+(-2) \Rightarrow -6 < 1\ \ \ \ (F)\\ \\ f)\ \ (8)(-5) > (-5)\cdot(8) \Rightarrow -40 > -40\ \ \ \ (F)\\ \\ g)\ \ 6(-4) < (-6)(4) \Rightarrow -24 < -24\ \ \ \ (F)[/tex]